Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.joc.6b00101
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Isomeric Effects of Ladder-Type Alkylated Terbenzodithiophene Derivatives

Abstract: A new class of heptacyclic ladder-type terbenzodithiophene (TBDT) structures merging three fused benzodithophenes was developed. Two TBDT conjugated isomers, named as syn-TBDT and anti-TBDT, where the two thienyl rings in the outmost BDT units are in the syn- and anti-fashion, are designed. Two decyl groups are introduced to their 6,13 and 7,14-positions to form four isomeric 6,13-syn-TBDT, 7,14-syn-TBDT, 6,13-anti-TBDT, and 7,14-anti-TBDT structures which are constructed by the DBU-induced 6-benzannulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Palladium‐catalyzed Sonogashira coupling reaction of 1,4‐diethynyl‐2,5‐dithiomethylbenzene ( 1 ) with 2‐iodothiophene ( 2 ) furnished the compound 3 . Reaction of 3 with I 2 resulted in the formation of the central iodinated BDT moiety in 4 . Palladium‐catalyzed benzannulation between an iodobiaryl and 1,2‐dialkylacetylene has been described by us previously .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Palladium‐catalyzed Sonogashira coupling reaction of 1,4‐diethynyl‐2,5‐dithiomethylbenzene ( 1 ) with 2‐iodothiophene ( 2 ) furnished the compound 3 . Reaction of 3 with I 2 resulted in the formation of the central iodinated BDT moiety in 4 . Palladium‐catalyzed benzannulation between an iodobiaryl and 1,2‐dialkylacetylene has been described by us previously .…”
Section: Resultsmentioning
confidence: 91%
“…Reaction of 3 with I 2 resulted in the formation of the central iodinated BDT moiety in 4 . Palladium‐catalyzed benzannulation between an iodobiaryl and 1,2‐dialkylacetylene has been described by us previously . Compound 4 was reacted with 1,2‐bis(5‐octylthiophen‐2‐yl)ethyne in the presence of Pd(OAc) 2 and pivalic acid to give TBDT‐4T with four octylthiophenyl groups at 6, 7, 13, and 14 positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile when recalling the common isomeric phenomena in organic electronics, it is well-known that isomerization has a significant effect on the thermal-, optical-, and electrochemical-properties, charge carrier mobility, and eventually device performance. Very recently, the constitutional isomeric effects of NFAs just have been investigated, among which Zhan et al revealed that a NFA FNIC2 based on a thieno­[3,2- b ]­thiophene-fused benzo­[1,2- b :4,5- b′ ]­dithiophene core showed a red-shifted absorption, higher crystallinity, optimized morphology, and higher PCE of 13.0% than its isomer analogue FNIC1 (10.3%) . Huang et al developed configurational anti- and syn-isomers of dithienocyclopentapyrene-based NFAs, whereas the anti-isomer exhibited higher and more balanced hole/electron mobilities and thus better photovoltaic performance than the syn-isomer (6.07% vs 3.07%) .…”
Section: Introductionmentioning
confidence: 99%